Study of anthelmintic activity and acute toxicity of medicine of combined composition - Semchenko, Kateryna; Vyshnevska, Liliia; Polovko, Natalia (ScienceRise: Pharmaceutical Science, 2018)
Aim. The aim of the work is to investigate the anthelmintic activity and acute toxicity of the drug containing albendazole and praziquantel in the ratio (1:4) in relation to pathogens of ascariasis in pigs, toxocarosis and dipylidiosis in dogs. These pathogens belong to the class of nematodosis (ascariasis, toxocarosis) and cestodoses (dipylidiosis). Materials and methods. The studies were carried out in the coproscopic laboratory of the parasitology department of Kharkov State Zooveterinary Academy and by the standardized method of Füllbourne and the ‘Method for the quantitative determination of helminth eggs’ (patent No. 9265). Samples for the study in dogs were obtained in the CP “Center for Animal Welfare”. In order to study the degree of toxicity of the proposed combination of albendazole and praziquantel, blood samples of pigs before and in 24 hours and 72 hours after the drug administration were taken for carrying out morphological and biochemical studies. Results. The results obtained indicate the presence of anthelminthic activity of the studied drug in relation to pathogens of ascariasis, toxocarosis and dipylidiosis. The parameters of hematological studies in pigs free from intestinal helminthes before and after 24 and 72 hours after intake the drug were within the limits of the physiological norm. Findings of the clinical examination of the animals of the two experimental groups showed that the behavior of the animals did not change (natural), the intake of food and water was normal, the visible mucous membranes were pale pink, the skin was intact, without damage and elastic. Conclusion. Thus, the proposed drug shows high level of anthelminthic activity in relation to pathogens of ascariasis, toxocarosis and dipylidiosis. The degree of its toxicity corresponds to “low toxic”. The obtained results indicate the advisability of the further research